Non-inflammatory cerebral amyloid angiopathy as a cause of rapidly progressive dementia: A case study - Leonel Tadao Takada; Paulo Camiz; Lea T. Grinberg; Claudia da Costa Leite (Dementia & Neuropsychologia)
Abstract A 77 year-old men developed a subacute-onset, rapidly progressive cognitive decline. After 6 months of evolution, he scored 6 on the Mini-Mental State Examination and had left hemiparesis and hemineglect. The patient died 11 months after the onset of cognitive symptoms. Brain MRI showed microhemorrhages on gradient-echo sequence and confluent areas of white matter hyperintensities on T2-weighted images. Brain biopsy revealed amyloid-b peptide deposition in vessel walls, some of them surrounded by micro-bleeds. In this case report, we discuss the role of cerebral amyloid angiopathy (CAA) in cognitive decline, due to structural lesions associated with hemorrhages and infarcts, white matter lesions and co-morbidity of Alzheimer's disease, as well as the most recently described amyloid angiopathy-related inflammation.